Pengaruh Budaya Kerja Islami dan Beban Kerja terhadap Kepuasan dan Kinerja Karyawan pada Rumah Sakit Islami Kendal - Akhmad Adi Darmawan; Asyhari Asyhari (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This analysis aims to evaluate the influence of Islamic Work Ethic and Task Load Level on Employee Productivity and Job Satisfaction at Kendal Islamic Hospital. Islamic Work Ethic in this study is measured through five main dimensions, namely siddiq (integrity), istiqamah (steadfastness), fathanah (intellectual intelligence), amanah (reliability), and tabligh (communication capacity). Meanwhile, Task Load Level is understood as work pressure reflected by three main indicators, namely physical fatigue, emotional fatigue, and psychological fatigue. This study uses a quantitative approach with an explanatory research design to test the causal relationship between variables. Primary data were collected through the distribution of structured questionnaires to hospital employees using probability sampling techniques, so that respondent representation is more assured. Data analysis was carried out using multiple linear regression through SPSS software, to determine the level of direct and indirect influence between variables. The results of the study indicate that Islamic Work Ethic has a positive and significant influence on Employee Job Satisfaction and Productivity, indicating that the application of Islamic values in work ethic can encourage motivation, loyalty, and performance. Conversely, the Level of Task Load has a significant negative effect on Job Satisfaction, indicating that excessive workload can reduce satisfaction, although it is not proven to have a significant impact on Employee Productivity. Furthermore, Job Satisfaction is proven to have a positive and significant influence on Employee Productivity, so it can play a role as an important mediating variable in the relationship between work ethic and performance. This study provides a theoretical contribution to the development of human resource management concepts based on Islamic values, while also offering practical recommendations for hospital managers to strengthen Islamic work ethic and manage workload proportionally to improve employee welfare and performance.